Clinical assessment of non‐suicidal self‐injury: A systematic review of instruments. (5th January 2021) - Faura‐Garcia, Juan; Orue, Izaskun; Calvete, Esther
Abstract: There has been an increase in the number of assessment instruments for non‐suicidal self‐injury (NSSI). However, previous reviews are inconsistent and do not provide a comprehensive psychometric assessment of the instruments. This study aimed to systematically assess and compare the psychometric properties of clinically relevant instruments to measure NSSI in any population. Through a systematic review guided by COSMIN and PRISMA, two searches were conducted in English and Spanish in February 2020 in 13 databases including grey literature. Of the 7, 813 initial records, 152 validations were extracted. From these, 83 instruments (22 versions or adaptations) were excluded for not measuring NSSI, having no potential clinical utility or not including psychometric properties. Finally, 26 (22 versions, 35 adaptations and 19 creations) instruments measuring NSSI were included. Predominantly, the studies were North American self‐reports in English for community adolescents, adaptations or versions emanating from a small number of instruments. Twenty‐six indicators were categorized to assess NSSI. The most frequent instruments are structured interviews, and their indicators were related to NSSI function and topography. Evidence of validity and reliability was positive but limited. Despite the high number of instruments and diversity of evaluations, we found no instrument with sufficient evidence for clinical assessment. Findings broadly overview NSSI assessment instruments' current use and future improvement in clinical and research settings.